PENERAPAN METODE PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IX-B SMP NEGERI 4 TAPUNG HULU KABUPATEN KAMPAR - Pharada Kresna (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research was conducted in order to know the results learning of IX-B grade students learn IPA SMP Negeri 4 Tapung Hulu academic year 2015/2016 with the implementation of cooperative learning. This research is a classroom action research, which was implemented in October and November 2015. The subjects were students of class IX-B SMPN 4 Tapung Hulu amounts to 34 students consist of 16 male dan 18 female. The data collection in this study using descriptive data analysis. Descriptive analysis of data on student learning outcomes obtained for result learning students. Result observation for result learning students, learners absorption before PTK is 73.8, after the first cycle is 83.8. Cycle II learning result is 87,9. From these data it can be concluded that the application of cooperative learning method can result learning outcomes IPA class IX-B SMPN 4 Tapung Hulu academic year 2015/2016.